Analyzing Electoral Choices: Determinants of PPP Voting Patterns in Sindh - Memon, Maheen (Journal of Development and Social Sciences, 2025)
The study is designed to assess the determinants of voting behavior in the success of political parties in Sindh Province. The study analyses factors such as socioeconomic factors, Biraderism, identity politics, and dynasty politics. The Pakistan People’s Party has consistently demonstrated its capability to maintain governance in the province of Sindh through elections since 2008. The People’s Party has maintained governance in the Sindh government since 2008. Sustaining the government for consecutive terms since 2008 till today is one of the important concerns, and the factors that have contributed to the sustainability of the PPP-only party in continuing its government in the province. For this research, a quantitative method was employed, and data were collected from N=101 eligible adult participants aged 20 to 60. Since the PPP had won three terms in a row from the same UCs, two UCs from Karachi and Sindh were chosen. SPSS has been utilized to quantify the data for this purpose. Cross-tabulation and a one-tailed test were used to obtain objective results and ensure validity and reliability. The results show that economic motivations, dynasty politics, and Biraderi influence voters’ behavior. The study’s results show that the democratic process in Sindh is fragile, and the fundamental right to vote is merely a communal endeavor. It is recommended that civil society, NGOs, and Election officials should educate and mobilize people, and that the media should play its critical role in developing awareness among people to make informed choices beyond loyalty to a party or any other social pressure group.